2017
DOI: 10.1051/matecconf/201712002009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pozzolime mixtures as a sustainable binder to replace portland cement in structural concrete

Abstract: Abstract. This study aimed to evaluate the properties of concrete mixes produced mainly of hydrated lime and different types of Pozzolan. This mixture, which is nominated as PozzoLime, is presented as an alternative sustainable binder to replace Portland cement in concrete. The study tends to optimize the Pozzolan to lime proportions with respect to workability and strength of concrete. The investigated parameters are; water to binder ratio, aggregate to binder ratio and type of Pozzolan. The effects of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Authors in [3] have invented a sustainable binder known as Pozzolime. This binder consists of hydrated-lime, silica-fume; and does not include Portland cement.…”
Section: B MIX Proportionmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors in [3] have invented a sustainable binder known as Pozzolime. This binder consists of hydrated-lime, silica-fume; and does not include Portland cement.…”
Section: B MIX Proportionmentioning
confidence: 99%
“…The environmental repercussions of the Portland cement production process have increased interest in limenatural Pozzolan cement during the last 50 years [2]. Kadum [3], created Pozzolime, a unique, sustainable binder composed of hydrated-lime, silica fumes, and fly ashes. Many studies have shown that the addition of fibers, especially steel fibers, to concrete can reduce the requirement for conventional reinforcement in certain circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…According to the previous research [5], and trail mix. It was selected two mixes for Pozzolime concrete (P1 and P2) and one mix for Pervious concrete, as illustrated in Table 3.…”
Section: Mixes and Curing Systemsmentioning
confidence: 99%
“…The pozzolanic reaction with lime is relatively slow, therefore, this mixture needs more than 28 days to develop such reliable strength [3]. Kadum et al [5] recently have developed a sustainable binder patented and called Pozzolime. This binder is a mixture of hydrated lime with silica fume, fly ash and included no Portland cement.…”
Section: Introductionmentioning
confidence: 99%
“…In the last 50 years, the environmental consequences of the Portland cement manufacturing process had prompted an increase in interest in lime-natural pozzolan cement [4]. In Iraq Pozzolime, a novel sustainable binder made from hydrated lime, silica fume, and fly ash, has been developed by Kadum et al [5]. The conceptualize of Pozzolime is based on the pozzolanic reaction between supplementary cementations materials, SCM and calcium hydroxide to produce calcium silicate hydrates similar to that produced by Portland cement hydration.…”
Section: Introductionmentioning
confidence: 99%